2018
DOI: 10.3329/bjas.v46i3.36314
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heat stress on milk yield and composition in early lactation of Holstein Friesian crossbred cattle

Abstract: The aim of the study was to know the effect of heat stress on milk yield and its composition of Holstein Friesian crossbred dairy cows rearing under intensive management system.Heat stress in dairy cows is caused by a combination of environmental factors i.e. temperature, relative humidity, solar radiation and air movement, etc. Grading-up of local cattle by temperate breeds for greater performance results to increase the sensitivity to heat stress. The trial was conducted during hot (May-July) and cool period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 6 publications
2
12
0
Order By: Relevance
“…Further, Kadzere et al [37] reported that milk fat, solids-not-fat, and milk protein percentage decreased 39.7, 18.9 and 16.9% respectively. Chanda et al [62] found that the milk fat, protein and lactose were significantly higher during the lower THI period compare to the higher THI period. In another study, decreased milk protein, lactose and fat values were recorded during the summer [70].…”
Section: Deterioration Effects Of Heat Stress On Milk Compositionmentioning
confidence: 98%
See 1 more Smart Citation
“…Further, Kadzere et al [37] reported that milk fat, solids-not-fat, and milk protein percentage decreased 39.7, 18.9 and 16.9% respectively. Chanda et al [62] found that the milk fat, protein and lactose were significantly higher during the lower THI period compare to the higher THI period. In another study, decreased milk protein, lactose and fat values were recorded during the summer [70].…”
Section: Deterioration Effects Of Heat Stress On Milk Compositionmentioning
confidence: 98%
“…To give a practical quantitative evaluation, Bernabucci et al [61] reported a loss of 0.27-kg milk per each temperature-humidity index unit incremental change. Chanda et al [62] found that the averages milk yield of both group one (G1) (Holstein-Friesian 50% × Local 50%) and group two (G2) (Holstein-Friesian 75% × Local 25%) were significantly higher in the cool period (14.92 and 19.54 l/d than in hot period (12.84 and 15.00 l/d for the G1 and the G2, respectively. The milk yield of the G2 group hampered more compare to the G1 due to higher THI during the hot season.…”
Section: Deterioration Effects Of Heat Stress On Milk Yieldmentioning
confidence: 99%
“…Heat stress refers to systemic indications in which the animal, affected by high temperatures, experiences rises in body temperature and physiological reactions occur in the hypothalamus, pituitary and adrenal cortex systems (Dikmen et al, 2009). W hen heat stress occurs, the productivity and quality of milk products from dairy cows decline (West et al, 2003;Liu et al, 2017;Chanda et al, 2018), heat stress may also cause disorders with the immune system making the cattle prone to infection by microorganisms or other diseases (Silanikove et al, 2015;Alemu et al, 2018); In addition, heat stress can also lead to low fertilization and decreased reproduction rates in cows (Andrade et al, 2008;Rahman et al, 2018). At the same time, parasitic diseases are widespread in high temperature and high humidity environments, which could potentially bring huge economic losses to certain cattle livestock industries.…”
Section: Introductionmentioning
confidence: 99%
“…At ambient temperatures of 29.4°C and 38.9°C, nutrient intake and milk yield decreased ~30.0% and ~27.6%, respectively [7 ,8 ]. In addition, buffalo have fewer sweat glands than do cattle, increasing heat sensitivity [3,9,10]. Thus, buffalo may be increasingly prone to heat stress as global warming progresses, threatening the buffalo dairy industry [11][12][13].…”
Section: Introductionmentioning
confidence: 99%